2010
DOI: 10.1353/jef.0.0020
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of State Regulations on the Costs of Public School Construction

Abstract: j o u r na l of e du c at i on f i na n ce against the benefits of the better "product" realized by these regulations; and third, a better understanding of the interactions among regulations within a state's whole regulatory environment is needed. i n troduc tion The public education construction sector has seen significant and unprecedented growth in the last decade (Filardo et al. 2006; Abramson 2007; Agron 2007). A recent analysis reports that the nation's public school districts spent more than $500 billio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 3 publications
2
19
0
Order By: Relevance
“…Almost all of the grantees and two‐thirds of the subgrantees reported that overall, Davis‐Bacon lead to wage and other cost increases (see Table ). These findings are in line with other research conducted over many years on the cost implications of Davis‐Bacon (e.g., Bilginsoy & Phillips, ; Dunn, Quigley, & Rosenthal, ; Fraundorf, Farrell, & Mason, ; Vincent & Monkkonen, ) though some studies have found to cost impacts (e.g., Duncan, ). Discussions with over a dozen subgrantees held during case study visits suggest that DoL adopted most of the wage rates that the subgrantees were already paying their in‐house staff but that wage rates for specialty jobs, such as for electricians working in multifamily buildings five floors or higher, rose quite substantially.…”
Section: Davis‐bacon: Unintended Consequencessupporting
confidence: 91%
“…Almost all of the grantees and two‐thirds of the subgrantees reported that overall, Davis‐Bacon lead to wage and other cost increases (see Table ). These findings are in line with other research conducted over many years on the cost implications of Davis‐Bacon (e.g., Bilginsoy & Phillips, ; Dunn, Quigley, & Rosenthal, ; Fraundorf, Farrell, & Mason, ; Vincent & Monkkonen, ) though some studies have found to cost impacts (e.g., Duncan, ). Discussions with over a dozen subgrantees held during case study visits suggest that DoL adopted most of the wage rates that the subgrantees were already paying their in‐house staff but that wage rates for specialty jobs, such as for electricians working in multifamily buildings five floors or higher, rose quite substantially.…”
Section: Davis‐bacon: Unintended Consequencessupporting
confidence: 91%
“…The effects of prevailing wage regulations on the operations of construction labor markets and on the cost of public construction have been the subject of considerable research (Azari‐Rad, Philips, and Prus , , ; Bilginsoy and Philips ; Dunn, Quigley, and Rosenthal ; Fraundorf and Farell ; Keller and Hartman ; Vincent and Mankkonen ). However, this literature has not addressed the question of the effect of prevailing wage regulations on the participation and bidding behavior of contractors.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent work has also looked at the impacts of facilities policies across all 50 states, with some attempting to understand the extent to which state policies impact the overall costs of educational facilities (Vincent & Monkkonen, 2010). Duncombe and Wang (2009) used data from the National Center for Educational Statistics (NCES) Common Core of Data School District Finance Survey, providing summaries of various types of state school building-aid programs.…”
Section: Research Comparing State Facilities Policiesmentioning
confidence: 99%
“…Although several studies have taken up facilities inequities across state lines (Filardo, 2016), facilities policy variation between states (Duncombe & Wang, 2009;Vincent & Monkkonen, 2010), and the actions of local school district leaders (Harris & Munley, 2002;Milder, 2011;Stover, 2012), in this study, we examine variation in facilities policy implementation in several districts even in close geographic proximity in the City of San Antonio, Texas.…”
Section: Research Objectivesmentioning
confidence: 99%